A development and biological safety evaluation of novel PVC medical devices with surface structures modified by UV irradiation to suppress plasticizer migration. Issue 9 (30th July 2013) - Haishima, Yuji; Isama, Kazuo; Hasegawa, Chie; Yuba, Toshiyasu; Matsuoka, Atsuko
Abstract : This study examines the chemical, physicochemical, and biological properties of PVC sheets treated with UV irradiation on their surfaces to suppress the elution of a plasticizer, di‐(2‐ethylhexyl) phthalate (DEHP), for developing novel polyvinyl chloride (PVC) medical devices. The PVC sheets irradiated under conditions 1 (52.5 μW/cm 2, 136 J/cm 2 ) and 2 (0.45 mW/cm 2, 972 J/cm 2 ) exhibited considerable toxicity in cytotoxicity tests and chromosome aberration tests due to the generation of DEHP oxidants, but no toxicity was detected in the PVC sheet irradiated under condition 3 (8.3 mW/cm 2, 134 J/cm 2 ). The release of DEHP from the surface irradiated under condition 3 was significantly suppressed, and mono‐(2‐ethylhexyl) phthalate (MEHP) converted from a portion of DEHP could be easily removed from the surface by washing with methanol. The physicochemical properties of the surface regarding the suppression of DEHP elution remained stable through all sterilizations tested, but MEHP elution was partially recrudesced by the sterilizations except for gamma irradiation. These results indicated that UV irradiation using a strong UV‐source over a short time (condition 3) followed by methanol washing and gamma sterilization may be useful for preparing novel PVC products that did not elute plasticizers and do not exhibit toxicity originating from UV irradiation. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A: 2630–2643, 2013.